Multi-objective optimization in biotechnological processes: Application to plant cell suspension cultures of Thevetia peruviana (2023)
Bioprocesses productivity is a compromise between two conflicting objectives, maximization of biomass growth rate and minimization of substrate consumption. In this work, a model based multi-objective optimization problem is solved for improving the process productivity in plant cell suspension cultures of Thevetia peruviana. A solution of the multi-objective problem allowed determining the optimal initial concentrations of substrate and biomass for assuring maximal productivity. Model-based optimization is carried out using a mechanistic model, which includes a representation of the intracellular processes taking place on the plant cells. The best solutions were chosen from the Pareto front in agreement with expert criterion. Results indicate that an initial inoculum concentration of 3.91g/L and an initial sucrose concentration of 23.63g/L, are recommended as initial conditions for obtaining a biomass productivity of 1.57g/L*day with an acceptable sucrose uptake. Experimental validation of the optimal found was carried out and the productivity obtained was 1.52g/L using an initial inoculum concentration of 4.27g/L and an initial sucrose concentration of 25.44g/L. Results suggest that the proposed methodology can be extended to increase the productivity in terms of metabolite production from this plant cell cultures and other plant species. © 2018, Universidad de Antioquia.